Clinical Data Warehouse Query and Learning Tool Using Human-Centered Participatory Design Process. - MULLIN, Sarah; Jane ZHAO; SINHA, Shyamashree; LEE, Robert; SONG, Buer; ELKIN, Peter L. (Studies in Health Technology & Informatics, 2018)
BMI Investigator (BMII) is an interactive web-based tool with a learning knowledge base, which provides a way for researchers to query structured, unstructured, genomic and image data contained in a data warehouse. We demonstrate how development of an efficient, usable, and learnable web interface for a diverse group of research stakeholders benefits from an iterative human-centered participatory design process utilizing a team of clinicians, students, programmers, and informatics experts.